Isolasi Fungi Tanah Kabupaten Situbondo serta Skrining Aktivitas Antibakteri Terhadap Pseudomonas Aeruginosa - Fawwas Batio Putra Pamungkas; Bawon Triatmoko; Ari Satia Nugraha (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Bacterial resistance to antibiotics is a serious concern. The search for new antibacterial compoundsfrom medicinal plants can result in overexploitation of natural ingredients. Therefore, it is necessary to search for new alternative sources. This study was aimed to fi nd new antibacterial agents derived from soil fungi isolated from swampy soil in the Pasir Putih Beach area of Situbondo Regency in inhibiting Pseudomonas aeruginosa (P. aeruginosa). Isolation was carried out using Potato Dextrose Agar (PDA) dissolved in sea water. The isolation results showed that 5 isolates fungi. The fungi IS-STB-III-4 and IS-STB-III-5 have the potential to inhibit bacterial using antagonist tests. Potential soil fungi were fermented for 14 days and extracted with ethyl acetate as a solvent. The extraction results were dissolved in 10% DMSO with a concentration series of 1000 μg /mL, 2000 μg/mL, 4000 μg/mL, 6000 μg/mL, 8000 μg/mL which will be used for antibacterial activity test using the disc diff usion method. The extract activity test showed results that were directly proportional to the extract concentration. The analysis and profi ling of the extract using High Performance Liquid Chromatography (HPLC) instrument showed that the extract contained alkaloids which were then isolated and identifi ed by HPLC.